Limited scientific publication of pre-graduate theses in a faculty of medicine in Lima, Peru, 2000-2009 - Taype-Rondán, Álvaro (2012)
Background: Authors of pre-graduate theses must try to publish them in scientific journals in order to support their quality and diffusion in the scientific-academic environment. Objectives: To determine Universidad de San Martin de Porres’ School of Medicine approved pregraduate thesis publication in the period 2000-2009. Design: Observational, descriptive. Materials: Pre-graduate theses approved during 2000-2009. Interventions: Permission was obtained to access theses at the University library. A search for separate theses was conducted utilizing Google Scholar to find dates of publication. Personal scientific production of both theses consultants and jurors was also researched. Results were tabulated in Microsoft Excel 2010 and presented descriptively. Main outcome measures: Theses publication, scientific production of tutors and juries. Results: During 2000-2009, 2 667 students graduated, 74 theses were approved, and only two were published. Twenty-one out of 67 consultants (31.3%) and 24 out of 73 jurors (32.9%) had at least one original article published. Conclusions: Low proportion of thesis publication was found at the faculty of Medicine studied.